Pengaruh Pengalaman Pelanggan, Citra Produk Lokal, Dan Suasana Kafe Terhadap Loyalitas Pelanggan (Studi Kasus Pada Cafe Sens Coffee and Space) - Fadhil, Sani; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of Customer Experience, Local Product Image, and Cafe Atmosphere on Customer Loyalty at Sen's Coffee and Space. The research was conducted using a survey method with 90 respondents, utilizing a saturated sampling technique. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. The data testing used is partial hypothesis testing (t-test). The results of the research show that Customer Experience, Local Product Image, and Cafe Atmosphere have a significant positive effect on Customer Loyalty. In conclusion, impressive Customer Experience, good Local Product Image, and a comfortable Cafe Atmosphere can increase Customer Loyalty at Sen's Coffee and Space. Keywords : Customer Experience, Local Product Image, Cafe Atmosphere, and Customer Loyalty.